OPTIMASI WAKTU MASERASI SILDENAFIL SITRAT DALAM JAMU KUAT YANG BEREDAR DI BOGOR BARAT - Harry Noviardi; Bina Lohita Sari; Muhamad Wildan Malik (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2016)
Herbal medicine is types traditional medicine that is consumed by people. One type of herbal medicine on the market is Jamu Kuat. According Indonesian Food and Drug Administration, herbal medicine can not contain chemical of drugs. But, Jamu Kuat on the market still found contain chemical of drug, that is sildenafil citrate. In previous research, analysis of sildenafil citrate in the Jamu Kuat has not been accompained by the optimization of extraction time.The aim of research is optimizing the time of maceration sildenafil citrate in Jamu Kuat circulating on the West Bogor. Sampling of Jamu kuat was used purpusive sampling. The sample macerated with constant stirring was used a magnetic stirrer with 560 rpm and analyzis with Thin Layer Chromatography and Spectrophotometry UV-Vis method. Results of the research show that there was 5 from 8 samples Jamu Kuat contained sildenafil citrate. Optimum times of maceration was 60-90 minutes in four samples, 120-150 minutes in one sample and contains sildenafil citrate 8.00-11.00% in four samples and 20.00-21.00% in one sample. The results was concluded there different optimal times for samples